Association Between Testosterone and Mortality Risk Among U.S. Males Receiving Dialysis - Yu, Jerry (Am J Nephrol, 2017)
BACKGROUND: In the general population, low circulating testosterone levels are associated with higher risk of cardiovascular disease and death. While testosterone deficiency is common in dialysis patients, studies of testosterone and mortality in this population have been mixed. We hypothesized that lower testosterone levels are associated with higher mortality in male dialysis patients. METHODS: We examined a nationally representative cohort of male dialysis patients from a large US dialysis organization who underwent one or more total testosterone measurements over 1/2007–12/2011. The association between total testosterone categorized as quartiles and all-cause mortality was studied using Cox models adjusted for expanded case-mix and laboratory covariates. We also examined total testosterone as a continuous predictor of all-cause mortality using restricted cubic splines. RESULTS: Among 624 male dialysis patients, 51% of patients demonstrated testosterone deficiency (total testosterone <300ng/dl); median (IQR) total testosterone levels were 297 (190, 424) ng/ml. In expanded case-mix+laboratory adjusted Cox analyses, we observed a graded association between lower testosterone levels and higher mortality risk (ref: Quartile 3): adjusted HRs (95% CI) 2.32 (1.33–4.06), 1.80 (0.99–3.28), and 0.68 (0.32–1.42) for Quartiles 1, 2, and 4, respectively. In adjusted spline analyses, the lower testosterone—higher mortality risk association declined with higher testosterone levels until reaching a threshold of 400ng/dl above which risk plateaued. CONCLUSION: Lower testosterone levels were independently associated with higher mortality risk in male dialysis patients. Further studies are needed to determine underlying mechanisms, and if testosterone replacement ameliorates death risk in this population.